An examination of Demographic Factors Affecting Job Satisfaction among the Teachers Groups in Government Primary Schools in Libya - Abdeljalil Mohamed Alsiewi (مجلة الدراسات الاقتصادية, 2022)
The paper aims to study the impact of five variables of demographic (Gender, Marital Status, Age, Academic Qualifications and Length of Experience) on job satisfaction. Specifically, we predicted the (significant relationship) of demographic variables to job satisfaction. A multistage cluster sampling was used to collect data from public primary school teachers in Libya. Independent sample t-test and analysis of variance (ANOVA) were adopted to examine relationships among the demographic variables and job satisfaction. The demographic variables which were found to relate closely to job satisfaction among the teachers were: Gender, Age, Academic Qualifications and Length of Experience. Marital Status, however, had no significant effect on the job satisfaction of the teachers.